ANALYSIS OF VARIABLES AFFECTING PROPERTY VALUE IN HOUSING WITH GROWING HOUSE CONCEPT IN THE ADAMARIS RESIDENCE HOUSING, TANJUNG MORAWA, DELI SERDANG - Hanifatul Azha Lubis,; Sugiharto Pujangkoro,; Dwira Nirfalini Aulia, (Journal of Innovation Research and Knowledge, 2022)
The purpose of this research is to find out analysis of variables affecting property value in housing with growing house concept in The Adamaris Residence Housing, Tanjung Morawa, Deli Serdang. The location of this research is The Adamaris Residence Housing which is located on Jalan Limau Manis, Limau Manis Tanjung Morawa, Deli Serdang Regency, North Sumatra Province. This research lasted for two months, from April to October 2021. This research is a quantitative Research. The Adamaris Residence Housing which has two types of houses, namely canary type as many as 248 houses with a land area of ​​78m² and a building area of ​​23m² and castillo type as many as 112 houses with a land area of ​​104m² and a building area of ​​27m². The total number of samples obtained is 41 which is used as the end in determining the results of the study. Hypothesis testing in this study uses a partial test. The results show that location has a positive and significant effect on property value in The Adamaris Residence Housing. Price has a positive and insignificant effect on property value in The Adamaris Residence Housing. Environment has a positive and significant effect on property value in The Adamaris Residence Housing. Characteristic has a positive and significant effect on property value in The Adamaris Residence Housing.